1997
DOI: 10.1016/s0960-9822(06)00294-6
|View full text |Cite
|
Sign up to set email alerts
|

Activin has direct long-range signalling activity and can form a concentration gradient by diffusion

Abstract: The long-range signalling mechanism by which activin initiates the transcription of genes in a concentration-dependent manner depends on a process of rapid diffusion and the establishment of an activin gradient across the tissue. It cannot be explained by a relay or wave propagation mechanism. Activin itself is the signalling molecule to which distant cells respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 35 publications
8
80
0
Order By: Relevance
“…Our results are consistent with previous work showing that a morphogen gradient in early Xenopus embryos is achieved by diffusion through intercellular space (Gurdon et al, 1994;McDowell et al, 1997;Scholpp and Brand, 2004;Williams et al, 2004) and that morphogen spreading can extend through nonresponsive cells. In a recent work, we have shown that Xbra induction can be detected behind a transcytosis-deficient graft (Jullien and Gurdon, 2005).…”
Section: Gradient Formationsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous work showing that a morphogen gradient in early Xenopus embryos is achieved by diffusion through intercellular space (Gurdon et al, 1994;McDowell et al, 1997;Scholpp and Brand, 2004;Williams et al, 2004) and that morphogen spreading can extend through nonresponsive cells. In a recent work, we have shown that Xbra induction can be detected behind a transcytosis-deficient graft (Jullien and Gurdon, 2005).…”
Section: Gradient Formationsupporting
confidence: 93%
“…According to the first idea, the concentration of activin just outside the outer Xbra border would be similar to the background level in the most distant parts of the animal cap; if the second idea is correct, the activin concentration would be higher just outside the Xbra border than in a more distant region. To examine the activin concentration just outside the outer Xbra border, we performed the following functional tests, because the activin concentration is too low to measure directly (approximately 40 pMol, McDowell et al, 1997).…”
Section: Boundary Sharpening Is Not the Results Of A Change In Gradienmentioning
confidence: 99%
“…Although passive diffusion can form an activin gradient (54), recent studies highlight the role of endocytosis in shaping morphogen gradients. Successive rounds of endocytosis and resecretion have been proposed as one model for morphogen movement through tissue (55).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation is that the large number of additional activin binding sites generated from the transgene product in pyramidal cells trap activin molecules, thereby making them unavailable for activin receptors on interneurons. In view of the low level of activin in normal adult hippocampus 36 and the high diffusibility of activin, 37 this additional effect of the dominant-negative receptor approach might become relevant in our preparation. Alternatively, activin might act on pyramidal cells to control the expression and/or release of factors that modulate the activity of interneurons in a paracrine fashion.…”
Section: Discussionmentioning
confidence: 99%